Bandage contact lens and topical steroids are risk factors for the development of microbial keratitis after epithelium-off CXL. Issue 1 (16th February 2019) - Tzamalis, Argyrios; Romano, Vito; Cheeseman, Robert; Vinciguerra, Riccardo; Batterbury, Mark; Willoughby, Colin; Neal, Timothy; Ahmad, Sajjad; Kaye, Stephen
Abstract : Objective: To investigate the role of bandage contact lenses (BCL) and topical steroids as risk factors for the development of microbial keratitis after epithelium-off corneal collagen cross-linking (CXL). Methods and Analysis: Patients undergoing CXL between February 2011 and July 2017 were included. Patients were divided into two groups: those who were treated postoperatively with a BCL, topical antimicrobial and steroids (group 1) and those who received only a topical antimicrobial until healing of the epithelial defect before introduction of topical steroids (group 2). Results: 1273 eyes of 964 patients were included. Group 1 comprised 316 eyes and group 2 comprised 957 eyes. There were no significant differences in the presence of persisting corneal haze or scarring between the two groups (p=0.57). Microbial keratitis occurred in nine eyes (0.71% of eyes) of eight (0.83%) patients (one case was bilateral) out of 1273 eyes. Staphylococcus aureus was cultured from corneal scrapes in seven out of nine (77.8%) cases and from contiguous sites in the two cases. All cases occurred in group 1 (incidence=2.85%) and none in group 2 (p<0.0001). A greater proportion of patients who developed microbial keratitis were atopic (75%, p=0.4). Conclusion: The use of BCL and topical steroids prior to healing of the epithelium is a significant risk factor for microbial keratitis. S. aureus is the most common micro-organism and is likely to originate from an endogenous site. Not using a BCL and delaying the introduction of topical steroids until epithelial healing significantly reduce the risk of developing microbial keratitis without increasing the risk of persistent corneal haze.